Strategies for Full Inclusion. Project Report Number 89-4 - Minnesota Univ., Minneapolis. Inst. on Community Integration; York, Jennifer; Minnesota Univ., Minneapolis. Inst. on Community Integration ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
Seven papers discussing practical strategies and examples for designing and implementing inclusive educational programs for Minnesota public schools are presented. The papers include: (1) "Strategies for Achieving an Integrated Education for Middle School Learners with Severe Disabilities" (Jennifer York and Terri Vandercook); (2) "A Team Approach to Program Development and Support" (Terri Vandercook and Jennifer York); (3) "MAPS: A Strategy for Building the Vision" (Terri Vandercook and others); (4) "Designing an Integrated Education for Learners with Severe Disabilities through the IEP Process" (Jennifer York and Terri Vandercook); (5) "Instruction in Regular Education Classes for Students with Severe Disabilities: Assessment, Objectives, and Instructional Programs" (Cathy Macdonald and Jennifer York); (6) "Regular Class Integration: Beyond Socialization" (Jennifer York and others); and (7) "Does an "Integration Facilitator" Facilitate Integration?" (Jennifer York and others). (TJH)
Availability: Institute on Community Integration, University of Minnesota, 109 Pattee Hall, 150 Pillsbury Drive SE, Minneapolis, MN 55455.
Sponsoring Agency: Office of Special Education and Rehabilitative Services (ED), Washington, DC.
Sponsoring Agency: Minnesota State Dept. of Education, St. Paul.
Contract Number: 37010-57613.
Contract Number: ED-G008630347-88.
May also be available online. Address as at 14/8/18
Keywords: Elementary Secondary Education; Instructional Systems; Learning Disabilities; Mainstreaming; Middle Schools; Program Design; Program Development; Program Implementation; Public Schools; Regular and Special Education Relationship; Rehabilitation Programs; Severe Mental Retardation; Social Integration; Special Education; State Programs; Inclusive Educational Programs -- Minnesota; Collected Works, General; Reports, Evaluative